Evaluation of Clinical and Radiographic Results of Cemented Total Hip Arthroplasty in 477 Patients - Guydo Marques Horta Duarte; Luiz Ronaldo Alberti (Revista Brasileira de Ortopedia)
Abstract Objective The purpose of the present study was to evaluate retrospectively the clinical and radiographic results of total hip arthroplasty (THA) performed with the Exeter technique and using the Exeter prosthesis. Methods Between March 2000 and December 2006, 504 THAs were performed in 477 patients, with several etiological diagnoses. A total of 260 surgeries were performed on the right side, 244 on the left side, and 27 were performed bilaterally. The mean age of the patients was 58.9 (17.7-86.8) years old, with a median of 69.0 years old. The preoperative planning was performed with appropriate templates. All of the surgeries were performed through the posterolateral approach with the patient placed on lateral decubitus. The clinical evaluation was performed according to the Harris hip score (HHS). In the radiographic evaluation, the bone cement interface in the three zones of DeLee and Charnley on the acetabular side and in the seven zones of Gruen on the femoral side were studied. Subsidence of the femoral component, presence of diaphyseal hyperthrophy, and heterotopic ossification were also observed. Results The mean follow-up of 441 surgeries (87.5%) was of 7.2 (1.0-16.6) years, with a median of 7.1 years. The incidence of complications was: dislocation, 3.2%; infection, 2.2%; peripheral nerve disorders 2.0%; thromboembolism 2.7%, acetabular cup loosing 2.0%; diaphyseal hypertrophy, 1.26%; distal migration of the femoral component between 2,0 mm and 2.9 mm, 0.5%; 1 case of aseptic loosing of the femoral component and 9 (1.8%) of the acetabular component. The mean HHS was mean 92.3 (50-100) points. Conclusion Cemented THA, with themethodology applied, proved to be an effective treatment for this group of patients. The results were satisfactory with acceptable complication rates.